Comparative Analyses of Regeneration Potentiality of Eight Indigenous Aromatic Indica rice (Oryza sativa L.) Varieties - Paul, Saikat; Roychoudhury, Aryadeep (International Journal of Scientific Research in Biological Sciences, 2019)
The development of an efficient in vitro regeneration system for economically-important aromatic rice cultivars is of urgent need for undergoing crop improvement through genetic modification. In the present work, comparative analysis of in vitro callus induction and regeneration efficiency of eight indigenous aromatic rice cultivars, viz., Kalonunia (KN), Gobindobhog (GB), Pusa Basmati (PB), Tulaipanji (TP), Radhunipagal (RP), IET 21261 (IET), Gandheswari (GN) and Radhatilak (RT) was carried out. The matured seeds were used as explants on Murashige and Skoog (MS) medium supplemented with 3 mg L-1 2,4-dichlorophenoxyacetic acid and 30 g L-1 sucrose for callus induction, while embryogenic calli were transferred to MS medium supplemented with combination of hormones, 1 mg L-1 naphthalene acetic acid, 2 mg L-1 6-benzylaminopurine and 4 mg L-1 kinetin for plant regeneration. The present study showed that all the varieties exhibited a high frequency of callus induction, ranging from 63.19% to 98.33%. The plant regeneration potential ranged from 93.43% to 33% depending on the genotypes examined. The maximum plant regeneration (%) was noted in KN (93.43%) followed by GB (90.83%), TP (89.34%), RP (89%), IET (75.92%), GN (74.66%) and RT (71%), whereas the minimum regeneration potential was observed in PB (33%). The regeneration potential was highly correlated with callus browning and callus production. The in vitro regenerated plants showed successful rooting and were well acclimatized under the conditions in growth chamber. Our observation highlighted a significant effect of genotype on callus induction ability, embryogenic response and plant regeneration capacity, suggesting the varietal difference in regeneration efficiency among the selected aromatic rice varieties.